ANALISIS PENGARUH INDEKS LQ45, INDEKS HARGA SAHAM GABUNGAN (IHSG) DAN SUKU BUNGA BI TERHADAP KINERJA REKSADANA SAHAM (Periode Januari 2010-Desember 2011) - Agus Safari Setiawan (2013)
his research was conducted to examine the effect of variable LQ45, JCI and Interest Rate BI to Performance Equity Fund. The population in this study were 99 Corporate Equity Fund transaction reporting company in Bapepam-LK period January 2010 to December 2011. Data were obtained from published reports of corporate transactions. The number of samples obtained by 37 companies. The analysis technique used is multiple linear regression and hypothesis testing using a confidence level of significance of 5%. The results showed that the variables LQ45 index, stock index and interest rate BI significant positive effect on performance Equity Fund. we suggest to prospective investors to pay attention to other factors that affect the performance of the Equity Fund in making an investment decision.